SURVEY OF FAULT DETECTION ALGORITHM IN WSN - Kumar, Vijay (International Journal of Research -GRANTHAALAYAH, 2017)
In recent years, applications of wireless sensor networks (WSNs) have been improved due to its vast potential to connect the physical world to the virtual world. Also, a progress in microelectronic fabrication technology reduces cost of developed portable wireless sensor nodes. Faults occurring to sensor nodes are familiar due to the sensor device itself and the harsh environment where the sensor nodes are deploy. WSNs is mainly affect by the crash of sensor nodes. Possibility of sensor node failure increases with increase number of sensors. Wireless sensor networks have been recognized, at an early stage in their development, to be a useful measurement technology for environmental monitoring applications. Based on their independence from accessible infrastructures, wireless sensor networks can be deploy in virtually any location and provide sensor samples in a spatial and temporal resolution.